Dietary Intervention Accelerates NASH Resolution Depending on Inflammatory Status with Minor Additive Effects on Hepatic Injury by Vitamin E Supplementation - Klaebel, Julie Hviid (Antioxidants (Basel), 2020)
Despite the lack of effective pharmacotherapy against nonalcoholic steatohepatitis (NASH) and liver fibrosis, vitamin E (vitE) supplementation and lifestyle modifications are recommended for the management of NASH due to promising clinical results. We recently reported a positive effect of supplementation with 800 IU vitE and atorvastatin on NASH resolution in guinea pigs. In the present study, we investigated the effect of high-dose vitE therapy combined with dietary intervention against progressive NASH and advanced fibrosis in the guinea pig model. Sixty-six guinea pigs received either high-fat (HF) or standard guinea pig chow diet (Control) for 25 weeks. Prior to eight weeks of intervention, HF animals were allocated into groups; dietary intervention (Chow) or dietary intervention with 2000 IU/d vitE supplementation (CvitE). Both Chow and CvitE reduced dyslipidemia, hepatic lipid accumulation and liver weight (p < 0.05), while CvitE further decreased hepatocellular ballooning (p < 0.05). Subanalyses of individual responses within intervention groups showed significant correlation between the hepatic hallmarks of NASH and lipid accumulation vs. inflammatory state (p < 0.05). Collectively, our results indicate that individual differences in sensitivity towards intervention and inflammatory status determine the potential beneficial effect of dietary intervention and high-dose vitE supplementation. Moreover, the study suggests that inflammation is a primary target in NASH treatment.